Stabilitas vitamin c selama peng olahan saribuah jambu biji (Psidium Guajava, L.)=Stability of Vitamine C during juice processing of guava (Psidium guajava, L) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
Guava fruit (PsidiuM guajava, 14) is a potential source of vitamine C. Reduction of vitamin C content in guava fruit during processing to fruitjuice cannot be eliminated. This research was aimed to study the fate of vitamin C in guajava fruit during processing to fruit juice. Conditions of juice processing conducted in this study were at room temperature (j 29Â°C)